Antioxidant activities, anticancer activity and polyphenolics profile, of leaf, fruit and stem extracts of Pistacia lentiscus from Tunisia - Yemmen, M.; Landolsi, A.; Ben Hamida, J.; Mégraud, F.; Trabelsi Ayadi, M. (Cellular and Molecular Biology, 2017)
Plant derived compounds have played an important role in the development of several clinically useful anticancer drugs. The aim of the present study was 1) to evaluate for the first time the anti-proliferative activity of a polyphenol enriched extract obtained from leaf, fruit and stem of Tunisian variety of Pistacia lentiscus against two cultured cancer cells, and 2) to carry out a phytochemical analysis of vegetable extracts particularly by determining the chemical composition of phenolics (total polyphenols, flavonoids and condensed tannins content in solvents with varying polarities), 3) to evaluate the antioxidant activity and identify the major compounds by RP-HPLC. Leaf extract using methanol/water (8:2) showed the highest polyphenol content (124.1 mg GAE/g DW). Moreover, total antioxidant capacity, reducing power and antiradical capacities against DPPH were maximal in leaf extracts with IC50 significantly lower than that standard (BHT). In MTT assay, methanol (8:2) extract exerted the most potent cytotoxic effect. The leaf extract exhibited an important antiproliferative activity (IC50: 135.67 ± 2.5 and 250.45 ± 1.96 Î¼g/ml in CaCo2 and AGS cells respectively) but the infusion extracts of fruit stems and leaves were inactive. The RP-HPLC analysis revealed the presence of several phenolic compounds in P. lentiscus leaf, fruit and stem including tannic acid, gallic acid, digalloyl quinic acid derivative, quercetin and p-coumaric acid as major phenolics. The high phenolic content and the important antioxidant activities of P. lentiscus extract could be a useful source of natural products and may be increasingly important for human consumption, prevention of damages caused by oxygen free as well as for the agro-food, cosmetic and pharmaceutical industries.